Improving Playing Skills: Implementation of Play-Teach-Play in Football Training for the 6-9 Years Old Group - Vicki Ahmad Karisman; Dedi Supriadi; Bangbang Syamsudar (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The aim of this research is to improve soccer playing skills in the 6-9 year old group through the implementation of Play-Teach-Play. Playing skills are very important for soccer players to be able to play well and effectively. Good and effective mastery during childhood will make it easier for soccer athletes to play well in the future. The research method used in this research is experimental with a pretest and posttest group design. The treatment was given in 7 meetings with a material focus in accordance with the Play-Teach-Play model. Participants in this research were 52 Football School students in the 6-9 year age group. The sample technique used was purposive sampling with the criteria, boys, aged between 6 and years. To obtain research data, all soccer athletes will be tested using the Game Performance Assessment Instrument (GPAI). The research results showed that there was a significant increase in the implementation of Play Teach-Play in soccer training for the 6-9 year old group. Play-teach-play effectively improves students' playing skills. The conclusion of this research is that playing skills can be improved through play-teach-play activities, students are required to practice according to real conditions in the field. Improving these skills will help students in handling real games.